Mobilizing Indigenous Knowledge through the Caribou Hunter Success Working Group - Hannah Atkinson (Land, 2020)
The caribou stewardship practices of the Iñupiat have persisted through cycles of abundance and decline for the Western Arctic Caribou Herd (WACH). This research seeks to address the challenges and opportunities faced when mobilizing Indigenous Knowledge in the National Park Service (NPS) management of the herd. Motivated by Indigenous stewardship concerns, NPS staff facilitate and participate in an informal working group focused on caribou hunter success. Using Indigenous Knowledge methods, this study examined the outcomes of the working group and the use of “rules of thumb” to identify and share stewardship practices. In the two cases, the Caribou Hunter Success Working Group created space for subsistence hunters to develop educational materials based on Indigenous Knowledge to address specific hunter success issues. Subsistence users participate in the federal subsistence programs and related subsistence forums, and it is the work of the NPS to mobilize the knowledge they contribute to improve subsistence management for both the users and the resource. There are two additional benefits for the NPS: (1) a better understanding of the use of the resource, and (2) when regulations are informed by Indigenous Knowledge, there is a greater likelihood of adherence. The mobilization of Indigenous Knowledge leads to more effective management.